PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK GAMBOGE PADA TOKO VERALSHOP.ID DI GUNUNG SINDUR - Pitri Yadita; Arif Siaha Widodo (Journal of Research and Publication Innovation, 2025)
His research aims to determine the influence of promotion and price on consumer purchasing decisions for Gamboge products at the Veralshop.id store in Gunung Sindur, Bogor. The type of research used in this research is quantitative research. The population used in this research includes all known customers who made purchases at the Veralshop.id Store. The sample used by the author in this research was 100 respondents. The data collection method used in this research is primary data. The primary data taken is the results of the questionnaire. The results of the research show that Promotion has a partial effect on Consumer Purchase Decisions for Gamboge products at the Veralshop.id Store in Gunung Sindur, Bogor as evidenced by the tcount > ttable or (6.193 > 1.984), this is also reinforced by the sig value < 0.05 or (0.000 < 0.05). Price partially influences consumer purchasing decisions for Gamboge products at the Veralshop.id Store in Gunung Sindur, Bogor as evidenced by the tcount > ttable or (6.765 > 1.984), this is also reinforced by the sig value < 0.05 or (0.000 < 0 .05). Promotion and Price simultaneously influence Consumer Purchase Decisions for Gamboge products at the Veralshop.id Store in Gunung Sindur, Bogor as evidenced by the value Fcount > Ftable or (31.816 > 3.09), this is also reinforced by the sig value. < 0.05 or (0.000 < 0.05).